Physiological and metabolic responses in broccoli plants fertilized with green manure - Watthier, Maristela; S. Oliveira, Franciele; L. Araújo, Wagner; Peralta Antonio, Nain; Henrique Silva Santos, Ricardo (Comunicata Scientiae, 2022)
Grasses and legumes affect differently the amount of N in the soil over time, mainly due to the differences in the chemical characteristics of its mass. Changes in the availability of N influence the absorption and assimilation of N, which will influence physiological processes in the plants. The objective of this paper is to evaluate the changes in gas exchange, chlorophyll fluorescence and biochemical activity in leaves of broccoli grown under different green manure amendments. The experiment was designed in a complete randomized block design, using the mass of jack bean (JB) and millet (M) pure and in mixtures and one control, totaling six treatments: Control, 100JB, 75JB25M, 50JB50M, 25JB75M, 100M, with four replicates. The canopy area, N content, gas exchange, and biochemical analyzes were evaluated on the broccoli index leaf 40 days after broccoli transplantation. The higher ratio of jack bean, the higher the canopy area, the N content and the amino acid, protein and malate content, and lower starch content, possibly due to the higher N mineralization in this green manure.